Color Calibration for Colorized Vision System with Digital Sensor and LED Array Illuminator - Zhenmin Zhu; Ruichao Song; Hui Luo; Jun Xu; Shiming Chen (Active and Passive Electronic Components)
Color measurement by the colorized vision system is a superior method to achieve the evaluation of color objectively and continuously. However, the accuracy of color measurement is influenced by the spectral responses of digital sensor and the spectral mismatch of illumination. In this paper, two-color vision system illuminated by digital sensor and LED array, respectively, is presented. The Polynomial-Based Regression method is applied to solve the problem of color calibration in the sRGB and CIE  L⁎a⁎b⁎ color spaces. By mapping the tristimulus values from RGB to sRGB color space, color difference between the estimated values and the reference values is less than 3ΔE. Additionally, the mapping matrix ΦRGB→sRGB has proved a better performance in reducing the color difference, and it is introduced subsequently into the colorized vision system proposed for a better color measurement. Necessarily, the printed matter of clothes and the colored ceramic tile are chosen as the application experiment samples of our colorized vision system. As shown in the experimental data, the average color difference of images is less than 6ΔE. It indicates that a better performance of color measurement is obtained via the colorized vision system proposed.